Impact of correcting the lymphocyte count to improve the sensitivity of TB antigen-specific peripheral blood-based quantitative T cell assays (T-SPOT.(®)TB and QFT-GIT) - van Zyl-Smit, Richard N; Lehloenya, Rannakoe J; Meldau, Richard; Dheda, Keertan (Journal of thoracic disease, 2016)
The standardized blood-based TB antigen-specific T cell assay, T-SPOT.(®)TB, is ~10% more sensitive than QuantiFERON(®)-TB-GIT (QFT-GIT) in detecting presumed latent TB infection (LTBI). Whilst T-SPOT.(®)TB uses a fixed number of lymphocytes per well, QFT-GIT uses a fixed volume of blood (~1 mL). However, the person-to-person lymphocyte count can vary by 2 to 3 fold. We hypothesized that this variability could explain the reduced sensitivity of QFT-GIT. The findings could have potential implications for improving case detection. T-SPOT.(®)TB was compared to QFT-GIT readouts before and after normalization of lymphocyte count (by adjusting the blood volume or lymphocyte enrichment within a fixed 1 mL volume) to an arbitrary value of 2.5×10(6) cells/mL. Within-test variability was evaluated to meaningfully interpret results. In patient-specific optimization experiments IFN-γ concentrations significantly increased when QFT-GIT positive samples were enriched with increasing concentrations of lymphocytes (1×10(6) vs. 2.5×10(6) cells/mL). However, for the group as a whole lymphocyte enrichment whilst maintaining a ~1 mL volume, compared to un-enriched samples, did not significantly increase IFN-γ [median (range): 0.03 (0-4.41) vs. 0.20 (0-2.40) IU/mL; P=0.64]. There was also no increase in IFN-γ readouts when QFT-GIT lymphocyte numbers were corrected (to 2.5×10(6) lymphocytes/mL) using volume adjustment. Interestingly, adjusted values were significantly lower than unadjusted ones [median (range): 0.02 (0-12.93) vs. 0.09 (0-14.23) IU/mL; P=0.008]. In QFT-GIT negative subjects lymphocyte enrichment did not increase QFT-GIT positivity rates. The reduced clinical sensitivity of the QFT-GIT assay, compared to T-SPOT.(®)TB, is likely to be due to factors other than lymphocyte count alone. Further studies are required to clarify these findings.